PENERAPAN PRINSIP GOOD GOVERNANCE PADA MASA PANDEMI COVID-19 DI KECAMATAN SEGERI KABUPATEN PANGKAJENE DAN KEPULAUAN - Pratiwi, Haerani; Sultan, Lomba; Ridwan, Muhammad Saleh (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
This study aims to determine the application of the principles of good governance, especially the principles of legal certainty and accountability in Segeri District, Pangkajene Regency and Islands during the Covid-19 pandemic. This research is a field research with normative theological and empirical juridical theological approaches. Based on the results of the study, it was found that the principle of legal certainty and the principle of accountability as part of the basic principles of good governance have been well applied, synergy between the government and the community is a fairly influential factor. While the Covid-19 pandemic did not have a significant impact, because the Segeri District Government continued to provide services even by making adjustments to implement health protocols, this did not reduce the quality of services to the community.